Design guidelines for supersonic stators operating with fluids made of complex molecules. (15th July 2020) - Anand, Nitish; Colonna, Piero; Pini, Matteo
Abstract: Supersonic stator vanes account for two-thirds of the fluid-dynamic losses in high temperature mini-Organic Rankine Cycle (ORC) turbines. As a result, the overall performance of the turbo-expander mainly depends on the design of the stator. Currently, there is no established correlation for the optimal design of such cascades. This work concerns an investigation about the accuracy of the only design method currently available for the design of supersonic stators operating with fluids made of complex molecules. A physics-based analytical model and a CFD-based model were developed to estimate the optimal post-expansion ratio and to compare their results with the Deych's model. The analysis shows that the Deych's method fails to accurately predict the optimum value of the post-expansion ratio. The study covers also the assessment of the optimum post-expansion ratio in relation to the solidity, the design flow angle and the total-to-static expansion ratio. The outcome demonstrates that there exists a unique optimum post-expansion ratio for a set of primary stator design parameters. In summary, vanes operating with a substance made of complex molecule as the working fluid, which is typical of high-temperature ORC turbines, feature a unique theoretical value of the optimum post-expansion ratio for a given total-to-static expansion ratio. New correlations are required to predict this value. Highlights: Developed an analytical model to study 2D loss mechanisms of supersonic stators. Demonstrated that Deych's model is not applicable to supersonic ORC stators. Characterized performance in terms of expansion ratio, solidity, blade angle, fluid. Demonstrated the need of new correlations for the design of ORC supersonic stators.